STUDENT PERCEPTION ON BENEFIT AND SIMPLICITY VIRTUAL LABORATORY UTILIZATION OF OPERATIONAL RESEARCH - Yusriyah, Kiayati; Ahmad, Salim (Jurnal Ilmiah Informatika Komputer, 2008)
This research is intended to analyze the perception of the students towards the use of operations research virtual laboratory. Technology Acceptance Mode is used for the analysis of the process of information technology adoption. MPT comprises of three main variables, namely perceived usefulness, perceived easy of use and the actual intention to use. A sample size of 60 Gunadarma University students are taken, comprise of 30 students from the faculty of industrial technology and 30 students from the faculty of economics. The result revealed that the most of the respondents perceive that the operations research virtual laboratory can be used only as complementary of the face to face laboratory practice. The correlation matrix indicates high positive correlation between perceived usefulness and perceived easy of use. These two variables altogether demonstrate a highly positive correlation with the variable of the actual intention to use.Keywords : MPT, perceived usefulness, perceived easy of use, Operation Research V-LabSubject Description : G.3.Probability and Statistic | Correlation and regression analysis | new